DIVISION XII: COMMISSION 6: ASTRONOMICAL TELEGRAMS. (13th August 2015) - Samus, N. N.; Yamaoka, H.; Gilmore, A. C.; Aksnes, K.; Green, D. W. E.; Marsden, B. G.; Nakano, S.; Lara, Martin; Pitjeva, Elena V.; Sphar, T.; Ticha, J.; Williams, G.
Abstract : IAU Commission 6 "Astronomical Telegrams" had a single business meeting during the Beijing General Assembly of the IAU. It took place on Friday, August 24, 2012. The meeting was attended by five C6 members (N. N. Samus; D. W. E. Green; S. Nakano; J. Ticha; and H. Yamaoka). Also present was Prof. F. Genova as a representative of the IAU Division B. She told the audience about the current restructuring of IAU Commissions and Divisions and consequences for the future of C6.